Phytochemical Analysis and Study of Molecular Docking of Leucaena leucocephala Leave Extract as Anticancer - Ariefin, Mokhamat; syarpin, Syarpin; Harianto, Bibit (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Cancer is a disease caused by unnatural cell growth in the body. It has become a disease with a high mortality rate in the world. Several therapies have been developed for cancer treatment, one of which is the exploration of the bioactivity of compounds contained in potentially medicinal plants. One of the potential medicinal plants that grows in Central Kalimantan province is L. leucocephala. In this study, the potential of L. leucocephala leaf extract was explored through phytochemical tests and molecular docking approaches. Based on the phytochemical test, it was found that L. leucocephala leaf extract contains flavonoids, terpenoids, and steroids. Based on the test results, a literature study was conducted on the flavonoids and terpenoids content in L. leucocepala leaf extract and molecular docking studies were conducted. Seven dominant compounds of L. leucocephala consisting of flavonoids and terpenoids were tested for their potential as inhibitors of receptor tyrosine kinase. The molecular docking results showed that flavonoid ligands (1-6) had more negative binding affinity values compared to the drug sunitinib, a common drug for cancer therapy, while terpenoid ligand (7) had less favorable binding energy. Based on the Lipinski rule of five test, ligands 1, 2, 4, and 5 fulfill all the criteria given as drug candidates, while ligands 3, 6, and 7 only fulfill 3 out of 5 criteria. Based on Lipinski rule of five and molecular docking, ligand 1,2,4, and 5 has potential to be anticancer.